Primary percutaneous coronary intervention for ST elevation myocardial infarction in nonagenarians. Issue 20 (13th July 2016) - Petroni, Thibaut; Zaman, Azfar; Georges, Jean-Louis; Hammoudi, Nadjib; Berman, Emmanuel; Segev, Amit; Juliard, Jean-Michel; Barthelemy, Olivier; Silvain, Johanne; Choussat, Rémi; Le Feuvre, Claude; Helft, Gérard
Abstract : Objective: To assess outcomes following primary percutaneous coronary intervention (PCI) for ST-segment elevation acute myocardial infarction (STEMI) in nonagenarian patients. Methods: We conducted a multicentre retrospective study between 2006 and 2013 in five international high-volume centres and included consecutive all-comer nonagenarians treated with primary PCI for STEMI. There were no exclusion criteria. We enrolled 145 patients and collected demographic, clinical and procedural data. Severe clinical events and mortality at 6 months and 1 year were assessed. Results: Cardiogenic shock was present at admission in 21%. Median (IQR) delay between symptom onset and balloon was 3.7 (2.4–5.6) hours and 60% of procedures were performed through the transradial approach. Successful revascularisation of the culprit vessel was obtained in 86% of the cases (thrombolysis in myocardial infarction flow of 2 or 3). Major or clinically relevant bleeding was observed in 4% of patients. Median left ventricular ejection fraction post PCI was 41.5% (32.0–50.0). The in-hospital mortality was 24%, with 6 months and 1-year survival rates of 61% and 53%, respectively. Conclusions: In our study, primary PCI in nonagenarians with STEMI was achieved and feasible through a transradial approach. It is associated with a high rate of reperfusion of the infarct-related artery and 53% survival at 1 year. These results suggest that primary PCI may be offered in selected nonagenarians with acute myocardial infarction.